2022
DOI: 10.3389/fgene.2022.910413
|View full text |Cite
|
Sign up to set email alerts
|

Impact of breeding for reduced methane emissions in New Zealand sheep on maternal and health traits

Abstract: Enteric methane emissions from ruminants account for ∼35% of New Zealand’s greenhouse gas emissions. This poses a significant threat to the pastoral sector. Breeding has been shown to successfully lower methane emissions, and genomic prediction for lowered methane emissions has been introduced at the national level. The long-term genetic impacts of including low methane in ruminant breeding programs, however, are unknown. The success of the New Zealand sheep industry is currently heavily reliant on the prolifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(27 reference statements)
0
4
1
Order By: Relevance
“…Aguerre et al (2018) have reported BCS heritability estimates of 0.25 for blond-faced Manech sheep. The present estimates were also higher compared to the ones reported for meat and wool sheep, most of which ranged from 0.04 to 0.32 (Walkom and Brown, 2017;Macé et al, 2018;Snyman and Fisher, 2019;Marques et al, 2020;Oliveira et al, 2021;Rodrigues et al, 2021;Hickey et al, 2022;Ramos et al, 2023a). However, one study reported estimates of New Zealand Merino ewes up to 0.66 depending on the reproductive stage (Tait et al, 2018).…”
Section: Genomic Heritabilitycontrasting
confidence: 70%
“…Aguerre et al (2018) have reported BCS heritability estimates of 0.25 for blond-faced Manech sheep. The present estimates were also higher compared to the ones reported for meat and wool sheep, most of which ranged from 0.04 to 0.32 (Walkom and Brown, 2017;Macé et al, 2018;Snyman and Fisher, 2019;Marques et al, 2020;Oliveira et al, 2021;Rodrigues et al, 2021;Hickey et al, 2022;Ramos et al, 2023a). However, one study reported estimates of New Zealand Merino ewes up to 0.66 depending on the reproductive stage (Tait et al, 2018).…”
Section: Genomic Heritabilitycontrasting
confidence: 70%
“…Although breeding is an effective strategy for reducing methane yield, traits like wool, live weight, and fat deposition may be impacted over time and should be watched closely [30]. Genetic selection for residual feed intake is an indirect method for reducing enteric methane (CH4) emissions in beef and dairy cattle (RFI).…”
Section: Selecting For Low-methane Producing Ruminantsmentioning
confidence: 99%
“…At that time, our thinking was constrained by three pre-conceptions: (a) methane production in the rumen was essential for taking up hydrogen ions and preventing acidosis, so blocking the process would kill the animal; (b) methane production was not a heritable trait; (c) feed additives could not reduce methane synthesis. The period 2006–2014 saw major advances in methane science, and all three pre-conceptions were rejected – we now have estimates of heritability ( 30 , 31 ) and a variety of novel forages and dietary additives that can reduce emissions [review: ( 32 )]. Moreover, blocking methane synthesis is not detrimental for the animal ( 33 ) – in fact, it improves animal efficiency because carbon that would have escaped by eructation is redirected into production ( 34 ).…”
Section: What Is the Future Of Food Produced From Livestock?mentioning
confidence: 99%